2020
DOI: 10.1177/0030222820984655
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Attitudes Towards Euthanasia: An Integrative Review

Abstract: We examine and integrate last two decades of research on euthanasia from a cultural perspective. After an exhaustive search from Scopus and Web of Science, 40 studies matching our criteria are included in the review. We qualitatively summarize the literature country-wise and use text map of co-occurring terms in the titles, keywords, and abstracts of these articles to determine the similarities and differences among sub-themes in continental clusters. Research done in Asian, European, North American, and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 127 publications
1
12
0
4
Order By: Relevance
“…A complete list of these variables, the rationale for their inclusion, and the data sources for each variable is provided in Table 1 ( Gielen et al, 2009 ; Tanuseputro, 2017 ; Pew Research Center, 2018 ; van Wijngaarden et al, 2019 ; Karumathil and Tripathi, 20202020 ; Hofstede Insights, 2021 ; Inglehart et al, 2021 ; The World Bank, 2021 ; Tran et al, 2021 ).…”
Section: Paradoxical Correlates Of Attitudes Towards Pas: Analyzing the Results Of The World Values Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…A complete list of these variables, the rationale for their inclusion, and the data sources for each variable is provided in Table 1 ( Gielen et al, 2009 ; Tanuseputro, 2017 ; Pew Research Center, 2018 ; van Wijngaarden et al, 2019 ; Karumathil and Tripathi, 20202020 ; Hofstede Insights, 2021 ; Inglehart et al, 2021 ; The World Bank, 2021 ; Tran et al, 2021 ).…”
Section: Paradoxical Correlates Of Attitudes Towards Pas: Analyzing the Results Of The World Values Surveymentioning
confidence: 99%
“…Cultural dimensions (power distance, individualism/collectivism, masculinity/femininity, uncertainty avoidance, long-term orientation, indulgence/restraint (2010)(2011)(2012)(2013)(2014) Cultural values and beliefs, and particularly individualism/ collectivism, appear to play a major role in shaping attitudes towards euthanasia and assisted dying. (Karumathil and Tripathi, 20202020) What do these results tell us? Though based on a relatively small number of countries, and not specifically addressing the specific case of dementia, they suggest that economic and cultural factors might play an important role in determining attitudes towards assisted dying, whether through the assistance or direct action of a physician.…”
Section: Rationale For Inclusion In Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since a significant number of participants in the present study reported a history of COVID-19, a possible reason for this finding could be the severe physical disability and weak cardiopulmonary function in the later stages of life in COVID-19 patients. Intercultural studies indicated that the unique characteristics of each culture play an important role in shaping attitudes toward euthanasia ( Karumathil & Tripathi, 2020 ). It should be noted that, from an Islamic point of view, euthanasia and DNR order have significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Following the screening process, 39 of the 996 identi ed studies were considered potential candidates for inclusion in the systematic review. Fourteen studies were excluded because they were not related to advance care planning (13,14,15,16,17,18,19,20,21,22,23,24,25,26). Additionally, 18 studies were excluded because they were different article types (27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44).…”
Section: Study Selectionmentioning
confidence: 99%